2022
DOI: 10.1007/s11910-022-01243-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response EEG: Current State and Future Directions

Abstract: Purpose of Review To critically appraise the literature on the application, methods, and advances in emergency electroencephalography (EEG). Recent Findings The development of rapid EEG (rEEG) technologies and other reduced montage approaches, along with advances in machine learning over the past decade, has increased the rate and access to EEG acquisition. These achievements have made EEG in the emergency setting a practical diagnostic technique for detecting seizures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A recent review on reduced montage, rapid response EEG approaches, which includes the precursor of the presented set up, concluded that these technologies are promising and can lead to a cost-effective solutions for neuromonitoring with reduced dependence on expert staff [ 14 ]. Nonetheless, there are still several research questions that need to be addressed through future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review on reduced montage, rapid response EEG approaches, which includes the precursor of the presented set up, concluded that these technologies are promising and can lead to a cost-effective solutions for neuromonitoring with reduced dependence on expert staff [ 14 ]. Nonetheless, there are still several research questions that need to be addressed through future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Under ideal conditions, neuromonitoring is performed in specialized centers via continuous or frequent intermittent EEG recordings, as well as through the interpretation of qualitative trends deriving from processed EEGs, such as the amplitude-integrated EEG: aEEG, in (predominantly neonatal) intensive care units [ 13 ]. However, long latencies to standard EEG initiation, even during regular working hours, have hindered its use for this indication, and have triggered the development of rapid emergent EEGs with reduced electrode montages [ 14 ]. Various commercial devices developed specifically for this purpose have been implemented and studied in adults [ 14 ], but none of them has been tested in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation